2016
DOI: 10.1053/j.semperi.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide therapy for pulmonary disorders of the term and preterm infant

Abstract: The 21st century began with the FDA approval of inhaled nitric oxide therapy for the treatment of neonatal hypoxic respiratory failure associated with pulmonary hypertension in recognition of the two randomized clinical trials demostrating a significant reduction in the need for extracorporeal support in the term and near-term infant. Inhaled nitric oxide is one of only a few therapeutic agents approved for use through clinical investigations primarily in the neonate. This article provides an overview of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 80 publications
0
23
0
1
Order By: Relevance
“…Subsequent individual-patient data meta-analysis suggested no specific benefit with prematurity and stated routine use could not be recommended [ 119 ]. Expert review of the topic resulted in consensus opinions from both the NIH and the American Academy of Pediatrics dissuading the routine use of iNO in premature infants [ 120 , 121 ]. Despite these statements, off-label use of iNO in extremely premature infants remains on the rise [ 122 ].…”
Section: Prevention Of Bpdmentioning
confidence: 99%
“…Subsequent individual-patient data meta-analysis suggested no specific benefit with prematurity and stated routine use could not be recommended [ 119 ]. Expert review of the topic resulted in consensus opinions from both the NIH and the American Academy of Pediatrics dissuading the routine use of iNO in premature infants [ 120 , 121 ]. Despite these statements, off-label use of iNO in extremely premature infants remains on the rise [ 122 ].…”
Section: Prevention Of Bpdmentioning
confidence: 99%
“…However, the use of inhaled nitric oxide to prevent BPD development in preterm infants was not successful. A meta-analysis of the studies of this topic published through January 2016 found no advantages, either when the gas was administered early after birth or when it was administered later [ 106 ], which explains why routine use of nitric oxide is not recommended by experts and scientific societies [ 107 , 108 ]. However, addition of vitamin A to nitric oxide administration can significantly improve final effect of nitric oxide inhalation [ 109 ].…”
Section: Prevention and Treatment Of Bronchopulmonary Dysplasia (Bpd)mentioning
confidence: 99%
“…For example, human and animal studies demonstrate decreased endogenous NO production and increased endothelin production in a variety of neonatal pulmonary hypertensive disorders . Endothelium‐based therapies including inhaled NO have improved outcomes, but these neonates continue to suffer significant morbidity and mortality …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Endothelium-based therapies including inhaled NO have improved outcomes, but these neonates continue to suffer significant morbidity and mortality. 22,23 Based on the emerging data that children conceived via ART exhibit vascular dysfunction similar to neonates with PVD, and that any IT including ART and NIFT may potentially complicate neonatal respiratory outcomes; the objective of this study was to determine potential differences in outcomes associated with clinical PVD in neonates born with any form of IT and controls. To this end, we conducted a large population-based study of neonatal pulmonary vascular disease (PVD) by using a California birth cohort.…”
Section: Introductionmentioning
confidence: 99%